ENHANCING BANKING SYSTEMS THROUGH BLOCKCHAIN TECHNOLOGY: A CURRENCY SITUATION STUDY - Blerta Leka (Mocka); Daniel Leka; Ariet Malaj (Agora International Journal of Economical Sciences (AIJES), 2023)
Blockchain technology, initially designed for cryptocurrencies like Bitcoin, has emerged as a powerful tool in the financial sector. This study explores its potential integration into the Albanian banking system. The Albanian banking sector, like others worldwide, faces challenges in currency management, security, and efficiency. The research assesses how blockchain can address these issues and aligns with Albania's existing regulatory framework. The study begins with an overview of Albania's banking sector, highlighting key regulations and practices. It emphasizes the limitations of traditional banking systems, particularly related to transparency, security, and cross-border transactions. Blockchain technology's key attributes, such as immutability and transparency, are examined as potential solutions. Specific blockchain applications in Albania, like cross-border payments, digital identity verification, and supply chain finance, are considered. The comparative analysis evaluates how blockchain can enhance efficiency, reduce transaction costs, and increase access to financial services in the Albanian banking system. It also highlights the need for regulatory adjustments to accommodate this technology. Challenges, including regulatory compliance, cybersecurity concerns, and interoperability, are addressed, along with strategies to mitigate them.This research provides a comprehensive view of the opportunities and challenges of blockchain technology in Albania's banking system, aiming to inform policymakers, financial institutions, and stakeholders about the potential benefits of adopting blockchain solutions while considering regulatory adjustments to create a secure and efficient financial landscape in Albania.
Keywords: 330